Penerapan Model Monitoring Dan Evaluasi Kepala Sekolah Sebagai Upaya Peningkatan Kinerja Guru Dalam Meningkatkan Capaian Mutu Sekolah - Kayatarno Kayatarno (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
Implementation of Government Regulation No. 19 of 2005 on the National Education System has implications for the assessment models and techniques implemented in the classroom. To produce completions that have intact abilities as expected in the curriculum of the education unit level, learners are expected to master the competencies set. Related to this, it is necessary to develop learning / competency training in a systematic and integrated manner, so that learners can master each competency thoroughly. The purpose of this school action research is to find out and analyze the extent of principal coaching that applies monitoring and evaluation models in an effort to improve teacher performance in improving school quality achievement. In this school action study conducted in 3 cycles, from the results of actions taken proven to improve teacher performance by achieving an average value whenever assessment or observation i.e., from 59.79 in cycle I, can increase to 69.37 in cycle II, and cycle III 85.75; with the completion of the group also from cycle I 29.17%, rose in cycle II to 79.17 % and finally in cycle III reached a completion of 100%. The results of this action study show that coaching through monitoring and evaluation can improve teacher performance in improving school quality achievement in SDN 3 Narmada District Narmada Kab. West Lombok Year of Study 2019-2020